Peculiarities of Juvenile Punishment in RA - Margaryan, A. (Bulletin of Yerevan University C: Jurisprudence, 2016)
One of the high priority tasks of any State is the prevention of juveniles՝ criminal behavior. In scope of this, the issue of criminal responsibility and punishment of crime perpetrators under the age of eighteen becomes of particular importance. The analysis of RA Criminal Code in force reveals the failure of the current system of punishments foreseen for the juveniles to ensure the adequate reaction to their criminal behavior and guarantee effective prevention. Unfortunately, due to the absence of effective measures alternative to imprisonment the latter yet remains the main punishment which is applied to the juveniles. The author suggests foreseeing of new types of punishment (deprivation of the right to engage in certain activities, restriction of freedom) and measures of educational character (ban on visiting certain places, placement in special educational institutions, participation in cultural, sport, educational and other restorative programs) in the criminal code of RA, which can be applied to the juveniles and will guarantee the adequate and proportionate state reaction to the criminal behaviour of juveniles.